2022
DOI: 10.3389/fimmu.2022.883079
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Neuraminidases in Immune-Mediated Diseases: Mucins and Beyond

Abstract: Mammalian neuraminidases (NEUs), also known as sialidases, are enzymes that cleave off the terminal neuraminic, or sialic, acid resides from the carbohydrate moieties of glycolipids and glycoproteins. A rapidly growing body of literature indicates that in addition to their metabolic functions, NEUs also regulate the activity of their glycoprotein targets. The simple post-translational modification of NEU protein targets—removal of the highly electronegative sialic acid—affects protein folding, alters protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 388 publications
0
10
0
Order By: Relevance
“…Fourth, we also reported that neuraminidases activation resulted in accumulation of circulating N -acetyl-neuraminic acid, a signaling metabolite that can trigger RhoA and Cdc42-dependent myocardial injury 21 . On account of their various functions, mammalian neuraminidases have been shown to play an emerging role in several human diseases, including autoimmune 22 , 23 , cardiovascular diseases 20 , 24 , 25 cancers 26 , neurodegenerative disorders 27 , and lung diseases 28 , 29 . Design of the specific inhibitors targeting neuraminidases have the potential to treat these diseases 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we also reported that neuraminidases activation resulted in accumulation of circulating N -acetyl-neuraminic acid, a signaling metabolite that can trigger RhoA and Cdc42-dependent myocardial injury 21 . On account of their various functions, mammalian neuraminidases have been shown to play an emerging role in several human diseases, including autoimmune 22 , 23 , cardiovascular diseases 20 , 24 , 25 cancers 26 , neurodegenerative disorders 27 , and lung diseases 28 , 29 . Design of the specific inhibitors targeting neuraminidases have the potential to treat these diseases 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“… a ND: no data available. b Referred from ref . c Modified from ref . Abbreviations: ApoB100, Apolipoprotein B100; ATG5, Autophagy related 5; CD protein, cluster of differentiation protein; EGFR, epidermal growth factor receptor; HGF, hepatocyte growth factor; IR, insulin receptor; LAP: latency-associated peptide; MMP9, matrix metallopeptidase 9; MUC1 , mucin 1; TGF-β, transforming growth factor beta; TLR, toll-like receptor; TrkA, Tropomyosin receptor kinase A . …”
Section: Introductionmentioning
confidence: 99%
“…The main reason for the poor characterization the mammalian sialidases could be due to their membrane-bound structure . More detailed information on the subcellular distribution, substrate specificity, catalytic properties, and amino acid homologies of the four mammalian sialidases can be found in recent review articles. ,, Despite the accumulating data, molecular mechanisms underlying mammalian sialidases involvement in cellular phenomena have yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations